Marjolin’s ulcer – a malignant lesion arising in chronic wounds and scars. Analysis of 8 cases - Zieliński, Tomasz; Lewandowska, Małgorzata (Dermatology Review/Przegląd Dermatologiczny, 2010)
Introduction. A malignant lesion which develops in a chronic wound or scar is known as Marjolin’s ulcer. The commonest type of neoplasm arising from Marjolin’s ulcer is squamous cell carcinoma (SCC), which is more aggressive than other primary SCC. Objective. Presentation of own experience in the treatment of Marjolin’s ulcer. Material and methods. Between 1993 and 2008 in the Clinic of Plastic, Reconstructive and Aesthetic Surgery of the University of Medical Sciences in Lodz, 12 patients with squamous cell carcinoma arising in scars and chronic wounds were treated. In this group, 8 patients were analyzed. We took into consideration such variables as: age of patient, location of lesion, time between the skin injury and carcinoma development, lymph node metastasis, organ metastasis and recurrence. As treatment, surgical excision of the lesion, closing the wound with sutures or using a free skin graft, were performed. In one case radiotherapy was used. Results. Burn scars were causative lesions of carcinoma in 6 patients. In one patient the carcinoma developed in posttraumatic scars and in chronic leg ulcer in another one. Marjolin ulcers were located on the legs (6), on the trunk (1) and in the axilla (1). There were 7 males and one female aged between 53 and 66 years. The time between the skin injury and carcinoma development ranged from 14 to 52 years. None of our patients had lymph node or organ metastases. In one case recurrence after excision of the lesion was observed. Conclusions. Chronic wounds and scars, especially on the legs, are connected with the risk of cancer development. Therefore in these patients increased oncological vigilance should be obligatory.